Machine learning for sustainable development - Hiran, Kamal Kant, 1982-; Khazanchi, Deepak; Vyas, Ajay Kumar; Sanjeevikumar, Padmanaban, 1978-; Alsharif, Futoon; Aluvalu, Rajanikanth; Bandhu, Kailash Chandra; Bashawyah, Doaa A.; Bhansali, Ashok; Chhabra Gandhi, Geeta; Dadhich, Manish; Dadhich, Shruti; et al. (De Gruyter frontiers in computational intelligence ;, 2021)
The book will focus on the applications of machine learning for sustainable development. Machine learning (ML) is an emerging technique whose diffusion and adoption in various sectors (such as energy, agriculture, internet of things, infrastructure) will be of enormous benefit. The state of the art of machine learning models is most useful for forecasting and prediction of various sectors for sustainable development.